Molecular Dynamics Simulation for Diffusion of H2/CH4 Mixture in Metal-Organic Framework Zn(tbip) - สีหามาตย์ คมพิชิต (KKU Science Journal, 2014)
Molecular dynamics simulations were used to study the diffusion of H2, CH4 and their equimolarmixtures inmetal-organic framework Zn(tbip) at 298 K. The results were analyzed to obtain the self-diffusivities ( Ds ) and the diffusion selectivities ( Sdiff ) of the molecules. In both pure and mixture, the Ds values of H2are in the range of 2.0×10-8 - 1.0×10-7 m/s andlarger than that of CH4, 3.0×10-9 - 2.0×10-8 m2/s. In mixtures, the diff S was determined to be different from the Knudsen selectivity ( Sdiff,Kn ), giving the values of Sdiff / Sdiff,Kn in the rage of 1-2.5. This different is attributable to the fact that methaneis more strongly adsorbed than hydrogen at pore walls of Zn(tbip). The Sdiff values are in the range of 3-7, indicating that Zn(tbip) can be useful for separating H2/CH4 mixtures.